C-abl and bcr are rearranged in a Ph1-negative CML patient. - Bartram, C R (1985)
Chromosomal analysis of a patient with chronic myelocytic leukemia (CML) revealed a translocation (9;12) (q34;q21) without a detectable Philadelphia chromosome (Ph1). Using molecular approaches we demonstrate (i) a rearrangement within the CML breakpoint cluster region (bcr) on chromosome 22, and (ii) a joint translocation of bcr and c-abl oncogene sequences to the derivative chromosome 12. These observations support the view that sequences residing on both chromosome 9 (c-abl) and 22 (bcr) are involved in the generation of CML and suggest that a subset of Ph1-negative patients may in fact belong to the clinical entity of Ph1-positive CML.